2018
DOI: 10.1080/03091902.2019.1576788
|View full text |Cite
|
Sign up to set email alerts
|

An ECG simulator with a novel ECG profile for physiological signals

Abstract: This work introduces a low-cost open-source electrocardiography (ECG) simulator comprising both MATLAB software for signal generation and a dedicated circuit board for signal output via a commercial sound card. Synthetic, rate-dependent ECG simulation is based on third-order polynomials that are calculated in sections for the main waves and spikes, respectively. Besides the heart rate, the output profile is fully adjustable with respect to Einthoven lead signals I-III, the amplitudes of the individual ECG wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 9 publications
0
4
0
3
Order By: Relevance
“…From the data, the distance between the first peak to the second peak is 1 second. It can be concluded that at the 60 th second, the peak point is 60, so the ppm value is 60 beats per minute [29]- [31]. In Figure 6 the distance between the first peak to the second peak is 0.75 seconds and so on is 0.66, 0.33, 0.35, and at the last peak is 0.35 (seconds).…”
Section: Ecg Signal Overviewmentioning
confidence: 88%
See 1 more Smart Citation
“…From the data, the distance between the first peak to the second peak is 1 second. It can be concluded that at the 60 th second, the peak point is 60, so the ppm value is 60 beats per minute [29]- [31]. In Figure 6 the distance between the first peak to the second peak is 0.75 seconds and so on is 0.66, 0.33, 0.35, and at the last peak is 0.35 (seconds).…”
Section: Ecg Signal Overviewmentioning
confidence: 88%
“…It can be concluded that in seconds-to-seconds experience irregularities. While in Figures 5 and 6 from the peak point to the next peak of 1 minute (60 seconds), which is under normal heart rate conditions [29]- [31].…”
Section: Ecg Signal Overviewmentioning
confidence: 96%
“…The further important area is testing of various signal processing techniques. In this context, we can test effectivity and robustness of signal processing methods via different simulated conditions, and consequently compare the results with the real ECG signals [36][37][38]. Lastly, the synthetic signals represent a significant area, frequently discussed in the research community, which enable create testing system for the cardiac pacemakers.…”
Section: Recent Workmentioning
confidence: 99%
“…Normalmente, el monitoreo de la frecuencia cardiaca se lleva a cabo en condiciones específicas del paciente: durante el reposo, en actividad física y en el sueño. Lo anterior, sumado a otras variables vitales y sintomatologías, permiten al médico hacer un diagnóstico de la salud del paciente [9]. La frecuencia cardiaca es uno de los signos vitales de mayor relevancia para los médicos, puesto que esta se ve afectada por diversos estímulos externos e internos al paciente.…”
Section: A El Monitoreo De La Frecuencia Cardiacaunclassified